Genomic profiling and sites of metastasis in non-small cell lung cancer - Chan, Kok Hoe; Sridhar, Arthi; Lin, Ji Zheng; Jafri, Syed Hassan Raza (Frontiers in Oncology, 2023)
Background We investigated the biological predisposition to site of metastasis in patients with NSCLC based on their molecular profiling and program death ligand PD-L1 status. We sought to identify any association between metastatic site and molecular profile in NSCLC patients. Methods This was a retrospective analysis of patients with stage IV NSCLC who were newly diagnosed from January 2014 to June 2022. Clinical characteristics, pathology, molecular reports, and imaging were retrieved and analyzed. Results A total of 143 patients were included in the study. Median age was 65 years, with an equal number of men (n=71) and women (n=72). The most common histology was adenocarcinoma (81.8%). At least one genetic mutation was discovered in 100 patients. Mutations with a targetable drug were found in 86 patients. The most common mutations were TP53 (25.2%), EGFR (24.5%), KRAS/NRAS (20.3%), and CDKN2A/2B (7.7%). Patients with any mutation were significantly more likely to have metastatic disease to the brain (57% vs. 37%, p=0.03), but there was no difference in metastatic disease to bone (34% vs. 26%, p=0.32). Patients without a discoverable mutation were significantly more likely to have metastatic disease to other sites (e.g., adrenal gland 91% vs. liver 66%, p=0.002). There was no difference in progression-free survival (PFS) or overall survival (OS) between those with versus without mutations. Median PFS and OS were significantly longer in patients with an EGFR mutation than those with KRAS/NRAS or TP53 mutations. Patients with PD-L1 >1% or TP53 were significantly more likely to have metastatic disease to organs other than bone or brain (p=0.047 and p=0.023, respectively). We identified four prognostic groups in metastatic NSCLC. Patients with PD-L1 <1% and no actionable mutations have the poorest prognosis, with median survival of around 20 months. Conclusion Patients with mutations discoverable on NGS are more likely to have metastatic disease to the brain. KRAS/NRAS in particular has a predilection to metastasize to the brain and bone. PD-L1 expression and a TP53 mutation, on the other hand, tend to lead to metastasis of NSCLC to organs other than brain or bone. These results need to be corroborated in larger prospective studies.